Interfaces of corporate social responsibility: a case study from vision system enterprise - Lucas, Michele Gaboardi; Martins Scheffer Demete, Carolini Danieli; Sehnem, Simone (Revista de Administração da UFSM, 2015)
The current article aims at analyzing the social responsibility practices of Vision System Enterprise in light of Carroll´s Model. Thus, a case study was performed, whose approach is qualitative. The where data collection was carried out through non-participant observation, semi-structured interviews, document analysis and questionnaire Competitiveness Award for Micro and Small Enterprises - (MPE) Brazil responded by organization. Among the results presented, it was possible to observe that the researched enterprise keeps precepts related to Corporate Social Responsibility in its daily practices. The practices which were adopted correspond to the requirements established by Carroll´s Model (1979), thus, this company has economical, legal, ethical and discretionary responsibilities. It works proactively towards social responsibility, fulfilling the issues related to consumption, environment, product safety and work. The enterprise´s challenge consists in keeping, updating and widening the practices already adopted. It was concluded that, by structuring its projects and programs, the researched enterprise accomplishes, spreads and evaluates several practices of corporate social responsibility, having highly involved employees.